Women’s Independence as an Embodiment of Family Hope Program in the Tamalanrea Village - Musrayani Usman; Mario Mario; Hariashari Rahim; Andi Muhammad Arif Haris; Atma Ras; Muhammad Rifki Pratama (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2023)
The social assistance of the Family Hope Program (PKH) is closely related to the cultural poverty that exists in beneficiary women. PKH carries out empowerment by using all the potential, natural resources or even human resources with the support of the government, so that the community becomes more independent. Based on the concept of empowerment theory with the using dimension and the theory of women’s empowerment from the Impact dimension, research data show PKH could not empower women individually or in groups (KPM). This research uses a qualitative approach, with data collection techniques are observation, interviews, and Focus Group Discussion (FGD). The results showed that 32 people could not understand and implement this independence because of education and understanding of the program or training provided. Social capital is a form of strengthening among these components.